2019
DOI: 10.3102/1076998619856590
|View full text |Cite
|
Sign up to set email alerts
|

Writing Process Differences in Subgroups Reflected in Keystroke Logs

Abstract: We used an unobtrusive approach, keystroke logging, to examine students’ cognitive states during essay writing. Based on data contained in the logs, we classified writing process data into three states: text production, long pause, and editing. We used semi-Markov processes to model the sequences of writing states and compared the state transition time and probability for demographic subgroups that were matched on writing proficiency. Results suggested that the subgroups employed different processes in essay w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Our own continuing work to advance the state of the art includes investigating the statistical properties of keystroke data (Guo, Deane, van Rijn, Zhang, & Bennett, ), trying to distinguish keyboarding skills from higher level writing skills (Deane et al., ), developing approaches to defining bursts of text personalized to the individual (as opposed to using a uniform threshold for all individuals) (Zhang, Hao, Li, & Deane, ), employing keystroke data to infer whether processes are consistent with the construct the test is designed to measure (Zhang, Zou, et al., ), and trying to model process durations and transitions (e.g., from text generation to editing) to see if they might suggest meaningful demographic group differences (Guo, Zhang, Deane, & Bennett, ). Ultimately, we and others will need to investigate and devise ways to report writing‐process information to teachers and students so that such information contributes to the development of more effective writing and writers.…”
Section: Discussionmentioning
confidence: 99%
“…Our own continuing work to advance the state of the art includes investigating the statistical properties of keystroke data (Guo, Deane, van Rijn, Zhang, & Bennett, ), trying to distinguish keyboarding skills from higher level writing skills (Deane et al., ), developing approaches to defining bursts of text personalized to the individual (as opposed to using a uniform threshold for all individuals) (Zhang, Hao, Li, & Deane, ), employing keystroke data to infer whether processes are consistent with the construct the test is designed to measure (Zhang, Zou, et al., ), and trying to model process durations and transitions (e.g., from text generation to editing) to see if they might suggest meaningful demographic group differences (Guo, Zhang, Deane, & Bennett, ). Ultimately, we and others will need to investigate and devise ways to report writing‐process information to teachers and students so that such information contributes to the development of more effective writing and writers.…”
Section: Discussionmentioning
confidence: 99%
“…This study offers a perspective considerably different from the existing literature on writing processes. Previous research has found notable process differences among demographic groups and between writing proficiency levels (Bennett et al, 2021, 2020; Guo et al, 2019). The current study documents the existence of subsets of individuals at the same proficiency level who, within a subset, employ processes similar to one another yet different from other individuals at that same level.…”
Section: Discussionmentioning
confidence: 94%
“…KL is an unobtrusive approach to get fine-grained process data on every keystroke during writing (Vandermeulen et al, 2020;Guo et al, 2019). Extensive empirical research with different orientations has been done on writing to discover the relation between KLs and underlying cognitive writing processes (Leijten & Van Waes, 2013).…”
Section: An Overview Of Kl Studiesmentioning
confidence: 99%